The effect of organizational culture, work discipline, and work experience on employee performance at PT. Omnikopi Kreasi Enak - Fadjari Widhi Kurniandra; Mohamad Trio Febriyantoro; Zulkifli Zulkifli; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto (Priviet Social Sciences Journal, 2022)
The objective of this study is to analyze and explain the effect of Organizational Culture, Work Discipline and Work Experience e on Employee Performance. The research belongs to explanatory research. The samples are taken by using purposive sampling technique and the size of the samples to be determined 34 employees of PT. Omnikopi Kreasi Enak. The data collecting technique is questionnaire. The data is analyzed by using SPSS software. The findings of this study show: Organizational Culture has insignificant effect on Employee Performance; Work Discipline has insignificant effect on Employee Performance; Work Experience has significant effect on Employee Performance